การพัฒนารูปแบบสร้างพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิของนักศึกษาหลักสูตรสาธารณสุขศาสตรบัณฑิต(สาธารณสุขชุมชน)วิทยาลัยการสาธารณสุขสิรินธร จังหวัดอุบลราชธานี - สนธิไชย อรรณพ (วารสารวิจัยการพยาบาลและสุขภาพ, 2018)
การวิจัยครั้งนี้เป็นการวิจัยและพัฒนา(Research and Development) โดยมีวัตถุประสงค์เพื่อ 1).ศึกษาสภาพการณ์อัตลักษณ์ของนักศึกษา 2). สร้างรูปแบบการพัฒนาพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิ และ 3). ประเมินผลการใช้รูปแบบการจัดกิจกรรมเพื่อพัฒนาพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิของนักศึกษาหลักสูตรสาธารณสุขศาสตรบัณฑิต (สาธารณสุขชุมชน)วิทยาลัยการสาธารณสุขสิรินธร จังหวัดอุบลราชธานี โดยมีการดำเนินการวิจัยออกเป็น4 ขั้นตอนคือ 1) การศึกษาสภาพการณ์อัตลักษณ์การให้บริการโดยศึกษาจากนโยบาย พ.ร.บ วิชาชีพสาธารณสุขชุมชน อาจารย์ และครูพี่เลี้ยง 2) เพื่อสร้างรูปแบบการจัดกิจกรรมเพื่อพัฒนาพฤติกรรมอัตลักษณ์ด้วยการระดมความคิดเห็นจากผู้เชี่ยวชาญ 3) ประเมินผลการใช้รูปแบบด้วยโดยจัดการประชุมอย่างเป็นทางการ(Connoisseurship) และ 4) ทดลองใช้กิจกรรมฯ โดยนำไปทดลองใช้กับ นักศึกษาหลักสูตรสาธารณสุขศาสตรบัณฑิต (สาธารณสุขชุมชน) วิทยาลัยการสาธารณสุข สิรินธร จังหวัดอุบลราชธานีรุ่นที่ 3 ตั้งแต่ชั้นปีที่1-4 จำนวน 49 คน วิเคราะห์ข้อมูลเชิงปริมาณโดยใช้ค่าร้อยละค่าเฉลี่ยส่วนเบี่ยงเบนมาตรฐานและการวิเคราะห์เปรียบเทียบ(t-test)ส่วนข้อมูลเชิงคุณภาพใช้การวิเคราะห์เชิงเนื้อหา (Content Analysis)ผลการวิจัย 1) ผลการศึกษาของวิทยาลัยฯในปีการศึกษา 2554-2557 พบว่า ด้านจิตบริการ ด้านการมีระเบียบวินัยและด้านใฝ่รู้ที่จะนำไปสู่ความเป็นวิชาชีพสาธารณสุขชุมชน อยู่ในระดับต่ำ 2) ผลการพัฒนารูปแบบการจัดกิจกรรมเพื่อพัฒนาพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิ ได้วงจรปฏิบัติการ 4 วงจรคือ วงจรที่ 1) “กิจกรรมค่ายปฏิบัติธรรม รักษาศีล และจัดโครงการเตรียมความพร้อมเป็นนักวิชาการสาธารณสุขชุมชน ณ บ้านเกิด” ในชั้นปีที่1. วงจรที่ 2) “กิจกรรมเรียนรู้จากปัญหาเป็นฐาน(PBL)” ในชั้นปีที่ 2. วงจรที่ 3) “กิจกรรมสร้างตน และเรียนรู้ปัญหาสิ่งแวดล้อมเป็นฐาน(CBL.)” ในชั้นปีที่ 3. และวงจรที่ 4) “กิจกรรมการเตรียมตน สู่วิชาชีพสาธารณสุขชุมชน” ในชั้นปีที่ 4 3).ผลการประเมินผลการใช้รูปแบบการจัดกิจกรรมเพื่อพัฒนาพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิหลังเข้าร่วมกิจกรรมของนักศึกษาสาธารณสุขชุมชนรุ่นที่ 3 ปีการศึกษา 2559 ทั้ง 3 ด้านพบว่า อยู่ในระดับมากที่สุด ( =4.54 SD=0.44) คือ ด้านจิตบริการ ด้านวินัย และด้านใฝ่รู้ในการปฏิบัติงานตามวิชาชีพสาธารณสุขชุมชน ( =4.75, 4.76และ4.43, SD=0.31, 0.29 และ 0.54 เรียงตามลำดับ) และผลการเปรียบเทียบประเมินผลการใช้รูปแบบการจัดการศึกษาเพื่อเสริมสร้างพฤติกรรมอัตลักษณ์การให้บริการสุขภาพระดับปฐมภูมิของนักศึกษาสาธารณสุข ก่อนและหลังการทดลองใช้มีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The Behavior Identity Model of Primary Health Care Services of Bachelor Degree Students in Public Health (Community Public Health) at Sirindhorn College of Public Health, Ubonratchathani. This research and development study was designed to identify the identity status of bachelor degree students in public health (Community Public Health) at Sirindhorn College of Public Health, Ubonratchathani, and to develop and to assess their identities of behavioral model of primary health care services. The study was conducted and comprised four steps of developing the identity of behavioral model of primary health care services of bachelor degree students in year 1 to year 4 at Sirindhorn College of Public Health, Ubonratchathani during 2011-2014. Firstly, the identities of health care services status were identified from exploring the Community Public Health Professional Act, public health lecturers and preceptors. The second stage was the creating activities in order to develop the identity of behavioral model. This stage was brain stormingby health professionals. The third step, verifying the identities of behavioral model was validated by Connoisseurship of 9 experts, and The fourth step was a testing model with the Bachelor Degree students in public health. Percentage, mean and standard deviation were applied for data analysis. Comparative analysis of the differences between before and after was conducted using t-test statistics and qualitative data using content analysis. The result reveals that the identity status including services mind, health professional discipline and inspiration for self-learning related to community public health was at a low level. Development and assessment model of identity of behavioral model of primary health care services includes 1) first year students have to attending a preparation for health professional and practicing Buddhism camp in their hometown, 2) second year students have to learn Problem Based Learning methods, 3) third year students have to study using Community Based Learning, and 4) fourth year students have to attend selves preparation activities for community public health professional. This model was assessed in 2016. The identity behaviors of primary health care services of year four students after attending all the activities were at the highest scores ( = 4.54 SD = 0.44). The identities of behaviors were services mind, discipline and inspiration for self-learning inspiration for self-learning related to community public health ( = 4.75, 4.76 and 4.43, SD = 0.31, 0.29 and. 0.54 respectively). A comparison before and after of behaviors showed the difference of identity of primary care service that there is statistically significant at the .05 level.